Estudo de efeitos vasculares, renais e citotóxicos do veneno da serpente Crotalus durissus cascavella - Evangelista, Janaína Serra Azul Monteiro (2008)
The snakes from the genus Crotalus in Brazil are represented by only one specie, Crotalus durissus. The poisoning by a sub-specie Crotalus durissus cascavella leads to systemic alterations, and is responsible for preliminary cause of death after the ophidic accident. This study aimed to evaluate the pharmacological effects of the snake venom Crotalus durissus cascavella - Ce (Cdcasca). This work looked at the actions of Cdcasca on the vascular system, assessing the physiological parameters of blood pressure and analyzing the histological changes in the heart, kidney, lung, brain and liver removed after the trials of blood pressure. The cytotoxic activity of Cdcasca was examined in four lines of human tumor cells: leukemia, breast tumor, colon tumor and nervous system tumor. There was an investigation of the likely mechanism of action of Cdcasca using the methods of viability cell by the exclusion of Trypan Blue, inhibition in the synthesis of ADN, antiproliferative activity of mononuclear cells (Alamar Blue). The integrity of the cell membrane, the ADN fragmentation and alteration of the mitochondrial transmembranic potential were analyzed by flow cytometry. It was Investigated the action of a Natriuretic Peptide (NPcasca) isolated from the venom of Cdcasca on a blood pressure system, on aortic rings assay and renal perfusion. After renal perfusion, the kidneys were subjected to histological analysis and study of its molecular biology. All parameters studied were analyzed by ANOVA and Student t-test, p <0.05. It was observed that the Cdcasca on the vascular system caused a significant decrease in heart and respiratory rates, and in the mean arterial pressure, with an increase in the production of nitric oxide in the blood of treated animals. There was made a pharmacological blockade with L-Name and the effects on heart and respiratory rates and mean arterial pressure were abolished. The total venom Cdcasca did not produced effects on the arteriolar mesenteric vascular bed. The whole venom Cdcasca was strongly cytotoxic on tumor line for leukemia, where there was a decrease in cell viability, as well as an increase in fragmentation of ADN. The NPcasca produced a decreased in heart and respiratory rates, and in the mean arterial pressure, with an increase in the production of nitric oxide in the blood of treated animals. In the experiments using NPcasca on aortic rings, there was a vasorelaxation dependent on endothelium. The NPcasca promoted a significant increase in perfusion pressure, and in renal vascular resistance. The urinary flow and the glomerular filtration rate also increased significantly. The perfused kidneys histological alterations were discrete, compared to the changes observed by the total venom Cdcasca. In experiments with isolated kidneys there was no change in gene expression of inflammatory mediators. Through these results we conclude that any component of poison Cdcasca is responsible for lowering effect and cytotoxicity in tumor cells. The NPcasca presented a hypotensive effects and increased the diuresis and natriurese. There was no change in gene expression of inflammatory mediators in kidney tissue.